Reflections on June 18 : contributions on the politics behind the events that occurred in the city of london on june 18, 1999. (S.l. : s.n., 1999)
The Global Carnival Against Capital took place on Friday, 18th June, 1999. It was an international day of protest timed to coincide with the 25th G8 Summit in Cologne, Germany. This publication is composed of original and reprinted articles about the protest held in London
44 p.